How We Treat Fever and Hypotension in Pediatric Hematopoietic Cell Transplant Patients - Zinter, Matt S.; Dvorak, Christopher C.; Auletta, Jeffery J. (Frontiers in Oncology, 2020)
Pediatric allogeneic hematopoietic cell transplant (HCT) survival is limited by the development of post-transplant infections. In this overview, we discuss a clinical approach to the prompt recognition and treatment of fever and hypotension in pediatric HCT patients. Special attention is paid to individualized hemodynamic resuscitation, thorough diagnostic testing, novel anti-pathogen therapies, and the multimodal support required for recovery. We present three case vignettes that illustrate the complexities of post-HCT sepsis and highlight best practices that contribute to optimal transplant survival in children.